Mixed convection in a lid-driven cavity with partially heated porous block - Colak, Eren; Ekici, Ozgur; Öztop, Hakan Fehmi (Pergamon-Elsevier Science Ltd, 2021)
In this study, the lid-driven cavity problem is investigated under mixed convection conditions by using Finite Volume Method (FVM). A porous block is placed in the middle of the domain with 0.1 porosity. A heater is placed on the edge of the porous block to imitate a local porous heater. In order to investigate the effects of the heater position on the problem physics, the heater is located in 4 different directions (left, right, top bottom) and 3 different orientations (clockwise, counterclockwise and middle). Mixed convection conditions are provided by three different Richardson numbers, 0.1 <= Ri <= 10 and porous block properties are applied by employing 4 different Darcy numbers 10(-7) <= Da <= 10(-1). It is observed that Darcy number can be used to control the vortex formation in the domain under specific configurations. Decrease in Darcy number can increase the average Nusselt number drastically, up to 10 times increase. Heater orientation can be used to control the heat transfer effectiveness, vortex shape and size. Heater orientation can increase the average Nusselt number by 324%. It is also shown that both heater location and orientation show a non-monotonic behavior for different flow parameters.
Keywords: Mixed convection; OpenFOAM; Lid-driven cavity; Porous media; Heater orientation